Dr. Esperanza Maribel Agoo won the best poster award - Agoo, Esperanza Maribel G. (Animo Repository, 2002)
Dr. Esperanza Maribel Agoo of the Biology Department, won the Best Poster Award during the First Global Taxonomy Initiative Workshop in Malaysia.